FUNDAMENTAL SCIENCE AND ENGINEERING - Valery P. Shestak (Moscow Polytechnic University, 2016)
The article deals with the formation processes of engineering tasks in the projects of fundamental science related to the class of mega8science, problems of use of the resulting knowledge to improve the professional level of the engineering corps and their importance for the development of Russia's economy.